(untitled) (Research, Society and Development, 2022)
Babassu and cashew palm trees are very abundant in Brazil, with the northeast region being the largest holder of these two plants. The babassu pie is made up of starch and is palatable with about 20% crude protein and 18% crude fiber. The liquid extracted from cashew nuts is a natural source of long-chain, unsaturated phenolic compounds. This work used natural agro-industrial by-products that were mixed and subjected to reaction. Electrosynthesis provided structural changes. ETBL was studied by FTIV, GC-MS, 13C NMR and TGA. ETBL has been proven to have high resistance to thermal degradation. The synthesis brings advantages to the environment, reduces the amount of phenolic residues, enables the socioeconomic and cultural activity of babassu.